Managing anxiety disorders in bipolar patients - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2023)
Anxiety disorders are among the main comorbidities encountered in patients with bipolar disease. Numerous clinical and epidemiological studies show an increased prevalence of anxiety pathologies (generalized anxiety disorder, social anxiety disorder, obsessive-compulsive disorder, panic disorder, and post-traumatic stress disorder) in bipolar subjects compared to the frequencies in the general population. Anxiety disorders are not without consequences on the evolutionary course of the mood disorder, including a significant reduction in euthymia time and less sensitivity to conventional medicinal therapies.